Socialization and Education About Haram Money in Fiqh Studies - Syifa Fauziyah; Alfina Putri Kusfiansyah; Ahmad Dhiyaauddin; Oyoh Bariah (al-Afkar, Journal For Islamic Studies, 2025)
Wealth is an essential need for human life; however, Islam emphasizes that the means of acquiring wealth must comply with sharia. Haram money, obtained through practices such as usury, gambling, and corruption, not only harms individuals but also negatively impacts society as a whole. This study discusses haram money from the figh perspective, aiming to enhance public understanding of the laws related to financial management in accordance with Islamic principles. In the context of modern economics, it is crucial to comprehend the consequences of using haram money, which can lead to social injustice and diminish individual integrity. This community service initiative involves socialization and education for the public, particularly the mothers of majelis taklim, about the importance of earning lawful income. The methods used in this activity include socialization through material delivery and discussions. Through an interactive approach, this activity aims to encourage behavioral changes in financial transactions and raise community awareness about the figh principles related to haram money.